Replication in Knowledge Transfer within MNC Subsidiary Episodes - Alias, Jamsari; Mat, Norazila (Journal of Ecohumanism, 2024)
With the rise in multinational corporations (MNCs), there is a greater need than ever to comprehend how parent businesses oversee their subsidiaries’ activities and impart knowledge to them. Japanese businesses have led the way in this area, implementing techniques like the Toyota Production System (TPS) to transfer the Japanese manufacturing ethos and uphold quality and control in their foreign operations. While there has been much discussion about the process of transferring Japanese manufacturing capabilities, little is known about how these methods are really acquired and integrated into the operations of the subsidiaries that are expected to employ them. This article looks at the parent company’s perspective on the transfer of manufacturing knowledge to the subsidiary. Thus, a comprehensive qualitative study was conducted in the Japanese multinational’s subsidiary, encompassing three major manufacturing initiatives (or philosophies): "TPS," "TPM," and "TS." Case data was gathered through 52 in-depth interviews with project participants, documentation, and moderate-participant observations. By using the subsidiary’s procedures, the formation of the entire process, and most importantly the utilization and development of episodes in snapshots to understand the process adds to our understanding of knowledge transfer. This article further elaborates how replication is a major element in episodic knowledge transfer.